Evaluating Adherence to Evidence Based Clinical Guidelines in Initial Management of Acute Biliary Pancreatitis in Academic Medical Center in Nepal - Shrestha, Sandesh; Bhujel, Sushim; Chaudhary, Bipin; Belbase, Narayan Prasad; Pradhan, Saroj Babu; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2025)
Background Acute biliary pancreatitis (ABP) is a common acute abdominal condition and is accompanied by potentially severe local or systemic complications, and high mortality. This study aimed to compare the current practice pattern in the management of ABP at our hospital with the recommendations provided by current guidelines. Methods A total of 55 patients with ABP managed between January 2024 and December 2024 were included in the study. Data were extracted from hospital records and reviewed for adherence to recommendations from recent guidelines on management of ABP. Compliance was calculated as a percentage of patients managed according to the recommendations from the guidelines. Results The majority of patients 35(63.6%) had mild ABP, followed by moderately severe 13(23.6%) and severe ABP 7(12.7%). The lowest adherence between daily clinical practice and recommendations included the implementation of early ERCP in patients with cholangitis with ABP (0%), the implementation of index cholecystectomy (14%), and the routine use of prophylactic antibiotics (35%). Conclusions The study demonstrated a generally low level of compliance to evidence-based recommendations for the treatment of ABP, with variability based on severity of ABP. Identifying gaps and implementing measures to address them allows for continued improvement in the management of patients with acute pancreatitis.